Pedro Páramo - Rulfo, Juan (Colección Literatura siglo XX, 2019)
Deserted villages of rural Mexico, where images and memories of the past linger like unquiet ghosts, haunted the imaginations of the author. In one such village of the mind, Comala, he set his classic novel Pedro Paramo, a dream-like tale that intertwines a man's quest to find his lost father and reclaim his patrimony with the father's obsessive love for a woman who will not be possessed, Susana San Juan.